#TITLE_ALTERNATIVE# - (NIM 20506062), MU'MINAH
Chitosan is modified chitin obtained from deacetylation of chitin. The presence of amine groups in chitosan increases its activity as it becomes a polycationic compound which is very useful for coagulation of turbid water. Since chitin is a natural polymer found in shrimp shells, chitosan is also biodegradable and environmental friendly. Therefore, the objective of this research is to use shrimp shell waste as the basic material for obtaining chitosan and to study the efficiency and effectiveness of chitosan as coagulant compared to tawas (aluminium sulphate). Chitin was first isolated from shrimp shells by removal of protein and minerals and the product was then deacetylated. The obtained chitosan was characterized using Fourier Transform Infra Red (FTIR) by which the degree of acetylation was determined. The viscosity-average molecular lecular weight (Mv ) was measured by using viscometric method. The clarification of turbid water was done using two kinds of turbid water, the first was a simulated turbid water of FeSO4 solution and the second was river water. It was found that chitosan could decrease 99,88% of the turbidity of both kinds of water using an optimum concentration of 4 ppm chitosan. On the other hand, tawas can only decrease 57,63% of the turbidity of simulated turbid water and 54,74% of the turbidity of river water, using an optimum concentration of 10 ppm tawas. Hence, it can be concluded that chitosan is much more efficient and effective as coagulant compared to tawas.